The Insula and Its Epilepsies. Issue 1 (January 2019) - Jobst, Barbara C.; Gonzalez-Martinez, Jorge; Isnard, Jean; Kahane, Philippe; Lacuey, Nuria; Lahtoo, Samden D.; Nguyen, Dang K.; Wu, Chengyuan; Lado, Fred
Insular seizures are great mimickers of seizures originating elsewhere in the brain. The insula is a highly connected brain structure. Seizures may only become clinically evident after ictal activity propagates out of the insula with semiology that reflects the propagation pattern. Insular seizures with perisylvian spread, for example, manifest first as throat constriction, followed next by perioral and hemisensory symptoms, and then by unilateral motor symptoms. On the other hand, insular seizures may spread instead to the temporal and frontal lobes and present like seizures originating from these regions. Due to the location of the insula deep in the brain, interictal and ictal scalp electroencephalogram (EEG) changes can be variable and misleading. Magnetic resonance imaging, magnetic resonance spectroscopy, magnetoencephalography, positron emission tomography, and single-photon computed tomography imaging may assist in establishing a diagnosis of insular epilepsy. Intracranial EEG recordings from within the insula, using stereo-EEG or depth electrode techniques, can prove insular seizure origin. Seizure onset, most commonly seen as low-voltage, fast gamma activity, however, can be highly localized and easily missed if the insula is only sparsely sampled. Moreover, seizure spread to the contralateral insula and other brain regions may occur rapidly. Extensive sampling of the insula with multiple electrode trajectories is necessary to avoid these pitfalls. Understanding the functional organization of the insula is helpful when interpreting the semiology produced by insular seizures. Electrical stimulation mapping around the central sulcus of the insula results in paresthesias, while stimulation of the posterior insula typically produces painful sensations. Visceral sensations are the next most common result of insular stimulation. Treatment of insular epilepsy is evolving, but poses challenges. Surgical resections of the insula are effective but risk significant morbidity if not carefully planned. Neurostimulation is an emerging option for treatment, especially for seizures with onset in the posterior insula. The close association of the insula with marked autonomic changes has led to interest in the role of the insula in sudden unexpected death in epilepsy and warrants additional study with larger patient cohorts.